Hubungan Antara Kesehatan Mental dengan Prestasi Akademik pada Siswa SMPN 36 Surabaya Selama Pembelajaran Daring di Masa Pandemi - Anggraini, Vannisa Intahaniya; Ansyah, Eko Hardi (Indonesian Journal Publisher, 2023)
This research was motivated by the phenomenon of the spread of the Covid-19 virus which resulted in all schools in Indonesia being closed during the pandemic and an online learning program was implemented. Online learning carried out at home makes most students feel bored and the demands obtained from schools such as assignments cause students to experience stress so that it will affect student learning outcomes. This study aims to determine the relationship between mental health and student achievement at SMPN 36 Surabaya during online learning during the pandemic. This research is a type of quantitative research with a correlational approach. The variables contained in this study were mental health as the independent variable and academic achievement as the dependent variable. This research was conducted at SMPN 36 Surabaya with a population of 594 students and the sample in this study was 225 students who were taken using the Stratified Random Sampling Technique. The data collection technique uses a mental health scale (reliability = 0.752) and for academic achievement by taking data that is already available, namely the UAS raport card score for even semesters. The analysis technique used Pearson's product-moment correlation with the help of the SPSS 16 program. The results of the data analysis of this study showed that the correlation coefficient (rxy) was 0.374 with a significance of 0.000 <0.05, which means that there is a positive relationship between mental health and academic achievement in students. SMPN 36 Surabaya during online learning during the pandemic. The effect of mental health on student academic achievement in this study was 14%.